Encounters with the Hidden Imam in Early and Pre-Modern Twelver Shīʿī Islam - Ghaemmaghami, Omid, (Islamic History and Civilization ;, 2020)
The history of Twelver Shīʿī Islam is a history of attempts to ‎deal with the ‎abrupt loss of the Imam. In Encounters with the Hidden Imam in Early and Pre-‎Modern Twelver Shīʿī Islam , ‎Omid Ghaemmaghami demonstrates that in the early years of what came to be known as the Greater Occultation, Shīʿī authorities maintained that all contact with the Imam had been sundered, forcing him to remain incommunicado ‎until his (re)appearance‎. This position, however, proved ‎untenable to maintain. Almost a ‎century after the start of the Greater Occultation, prominent scholars ‎began to concede the ‎possibility that some Shīʿa can meet the Hidden Imam. Accounts of encounters with the Imam from the Greater Occultation soon began to appear, adumbrating their exponential growth in later centuries.